Work Competency, Motivation And Discipline In The Police Personnel Force - Kharis Nur Rahman; Ellin Herlina; Mahfud (PT. Berkah Digital Teknologi, 2022)
Purpose of the study —to determine the effect of competence, motivation, and work discipline on the performance of POLRI personnel at the XYZ Resort Police of West Java. Research method—Quantitative study using the Survey method Result— There is a simultaneous positive effect of Competence, Motivation, Work Discipline on the Performance of POLRI Personnel at the XYZ Resort Police. The magnitude of the positive influence of Competence, Motivation, Work Discipline on the Performance of POLRI Personnel at the XYZ Resort Police is 90.6% while the remaining 9.4% is influenced by other factors. Conclusion— The variable with the greatest influence on the performance of POLRI personnel is the Competence variable, while the variable with the least influence is the Motivation variable.